2020
DOI: 10.4025/actascibiolsci.v42i1.46412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shading and nitrogen fertilization on nitrogen metabolism, essential oil content and antimicrobial activity of Achillea millefolium

Abstract: The Achillea millefolium L. is a perennial herb with important antibacterial, antifungal, anti-inflammatory, antitumoral, and antioxidant properties. This research aimed to investigate the effect of shading (75%; black net) and nitrogen fertilization (0, 75 and 150 kg urea ha-1) on the nitrogen metabolism, essential oil yield and antimicrobial activity of A. millefolium at vegetative- and reproductive-stage. The evaluated parameters varied depending on the organ and the phenological stage of the plant consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several groups have addressed the influence of light modification on EO metabolism in different plant species [40,60,61]. The EO content of marigold [62], chamomile [63] and yarrow [64] decreased with shading level, whereas sage [39] and oregano [29] were improved by limited light intensity.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…Several groups have addressed the influence of light modification on EO metabolism in different plant species [40,60,61]. The EO content of marigold [62], chamomile [63] and yarrow [64] decreased with shading level, whereas sage [39] and oregano [29] were improved by limited light intensity.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…Several literatures reported that the plants grown under low light intensity in closed environments exhibited better growth, yield, and enhancement of the secondary metabolites such as essential oils because of the reduction in the photosynthetic activity [ 13 ]. The enhanced essential oil content under low intensities was reported in yarrow ( Achillea millefolium L.) [ 14 ] and oregano ( Origanum vulgare L.) [ 15 ]. Thus, cultivation of medicinal and aromatic plants under controlled environments such as greenhouses, growth chambers, and playhouses provides a sustainable opportunity to enhance the principal chief phytochemicals, maximize the biomass yield, and in addition help to prevent the loss through insects and pests, and regulate both productivity and its production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Native to India, lemongrass is a perennial aromatic herb grown to obtain its essential oil, which is rich in citral, a substance used by the perfumery, cosmetics and pharmaceutical industries (May et al, 2008). Studies such as Pandey, Rai, and Acharya (2003), Jaramillo-Colorado, Palacio-Herrera, and Duarte-Restrepo (2020), Lima et al (2020), Lee, Garcia, Matinazzo, and Teodoro (2020), have demonstrated intense antimicrobial, antifungal, antiviral, and insecticidal activity of the essential oils. The objective in this study was to analyze the antifungal activity of lemongrass (Cymbopogon flexuosus) essential oil and citral for the control of the fungus Aspergillus flavus in in vitro tests and its proliferation in contaminated grains of wheat (Triticum aestivum).…”
Section: Introductionmentioning
confidence: 99%